Kesejahteraan Keluarga Petani Bawang Merah ( Alllium ascalonicum linn) di Nagari Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok - Rahma Wati; Dedi Hermon; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
Abstract The purpose of this study was to determine the basic needs of shallot farmers including (food, clothing, shelter), income, and health, in Nagari Alahan Panjang, Lembah Gumanti District, Solok Regency. This type of research is descriptive quantitative, with a population of family heads of onion farmers totaling 4,260 people. The sampling technique is Proportional Random Sampling with taking 5% in each jorong with a total sample of 212 people. Data collection techniques using questionnaires and data analysis techniques, Descriptive Statistics Analysis with percentage formulas. The results of the study show that: (1) Basic needs that cover food, clothing and family boards have been fulfilled, this can be seen from the fulfillment of good food requirements even though nutritional intake is still lacking, (2) The income of shallot farmers is only enough to meet basic needs . (3) The health of the onion farmer family is quite good, only a fever which is mostly experienced by farmers. (4) education of low shallot farmers because most of them are elementary school graduates. Keywords:Welfare,basicneeds,income,health,education